Cover Feature: Hydrophilic Crosslinked TEMPO‐Methacrylate Copolymers – a Straight Forward Approach towards Aqueous Semi‐Organic Batteries (ChemSusChem 18/2022). Issue 18 (31st August 2022) - Elbinger, Lada; Schröter, Erik; Friebe, Christian; Hager, Martin D.; Schubert, Ulrich S.
Abstract : The Cover Feature shows a schematic coin cell battery that is constructed from a metallic zinc anode, an electrolyte‐soaked separator, and an organic polymer composite cathode. In this cathode, a hydrophilic 2, 2, 6, 6‐tetramethylpiperidine‐ N ‐oxyl (TEMPO) radical‐bearing polymer is utilized as the redox active species. Through copolymerization with a hydrophilicity mediator, it was possible to enable aqueous electrolytes for the present battery system. This electrolyte is represented by the Erlenmeyer flask in the right half of the image that features representative zinc perchlorate ions in aqueous solutions. To emphasize the compatibility of aqueous organic energy storage systems with sustainable energy generation, the cell and the flask are positioned on an array of solar cells. More information can be found in the Research Article by L. Elbinger, E. Schröter, et al .